The mirror & the light - Mantel, Hilary 1952-2022 (4th Estate, 2020)
"England, May 1536. Anne Boleyn is dead, decapitated in the space of a heartbeat by a hired French executioner. As her remains are bundled into oblivion, Thomas Cromwell breakfasts with the victors. The blacksmith's son from Putney emerges from the spring's bloodbath to continue his climb to power and wealth, while his formidable master, Henry VIII, settles to short-lived happiness with his third queen, before Jane dies giving birth to the male heir he most craves.Cromwell is a man with only his wits to rely on; he has no great family to back him, no private army. Despite rebellion at home, traitors plotting abroad and the threat of invasion testing Henry's regime to breaking point, Cromwell's robust imagination sees a new country in the mirror of the future. But can a nation, or a person, shed the past like a skin? Do the dead continually unbury themselves? What will you do, the Spanish ambassador asks Cromwell, when the king turns on you, as sooner or later he turns on everyone close to him?"--Publisher description
Auf der Buchrückseite angegeben: "With 'The mirror & the light', Hilary Mantel brings to a triumphant close the trilogy she began with 'Wolf hall' and 'Bring up the bodies'."
Keywords: Cromwell, Thomas / Earl of Essex / 1485?-1540 / Fiction; Cromwell, Thomas; Great Britain; Fiction; Historical fiction; Biographical fiction; Great Britain / Court and courtiers / Fiction; Great Britain / History / Henry VIII, 1509-1547 / Fiction; Fiktionale Darstellung